Primary source regions of polychlorinated biphenyls (PCBs) measured in the Arctic - Ubl, Sandy; Scheringer, Martin; Stohl, Andreas; Burkhart, John F.; Hungerbühler, Konrad (Atmospheric Environment, 2012)
ISSN:1352-2310 ISSN:0004-6981 ISSN:1352-3260